Stenosing Crohn’s disease patients display gut autophagy/oxidative stress imbalance - Leonardo Schirone; Maria Carla Di Paolo; Daniele Vecchio; Cristina Nocella; Alessandra D’Amico; Riccardo Urgesi; Lorella Pallotta; Gianfranco Fanello; Giuseppe Villotti; Maria Giovanna Graziani; Mariangela Peruzzi; Elena De Falco; et al. (Scientific Reports, 2024)
Abstract In this pilot study, we assessed the role of autophagy in Crohn’s Disease (CD), particularly in patients with a stenosing phenotype. Through the analysis of biopsied specimens from 36 patients, including 11 controls and 25 CD patients, categorized into inflammatory and stenosing groups, we identified a significant reduction in the autophagosomal marker Lc3b-II in patients with active inflammation and stenosis. This was paralleled by an increase in oxidative stress markers, including sNOX2-dp and H2O2, and a decrease in the antioxidant capacity measured by HBA, suggesting an imbalance in autophagy and oxidative stress mechanisms. Additionally, our findings show a correlation between autophagy markers and oxidative stress levels, indicating that autophagy dysfunction may play a pivotal role in CD and in the progression of a stenosing disease phenotype, by failing to eliminate detrimental molecules and pathogenic bacteria, thereby promoting fibrosis. This study is the first to demonstrate in vivo autophagy inhibition in stenosing CD patients and suggests that stimulating autophagic processes could offer a new avenue for the prevention and treatment of intestinal fibrosis in CD. Our results highlight the importance of exploring the interactions between autophagy, the fibrotic process, and the inflammatory cascade, opening avenues for potential therapeutic interventions in CD management.